The Impact of Local Story Packaging, Educational Activities, and Traditional Branding on Destination Attractiveness through Positive Emotions in Yogyakarta - Chaniago, Anggrany; Muhtadi, Muhamad Ammar; Lesmana, Tera (West Science Social and Humanities Studies, 2025)
This study examines the role of local story packaging, educational activities, and traditional branding in enhancing destination attractiveness, with positive emotions as a mediating variable, in the context of cultural tourism in Yogyakarta, Indonesia. Using a quantitative approach with 250 respondents and data analysis employing Structural Equation Modeling–Partial Least Squares (SEM-PLS 3), the findings reveal that all three independent variables significantly influence positive emotions and destination attractiveness. Furthermore, positive emotions are shown to mediate these relationships, highlighting their central role in shaping tourists’ perceptions and experiences. The study contributes to tourism literature by confirming the importance of culturally grounded strategies in destination marketing and provides practical implications for stakeholders in developing emotionally engaging, authentic, and sustainable tourism experiences.